Intercalation of CoO in S‐Doped Graphite as High‐Performance Anodes for Lithium‐Ion Batteries. Issue 12 (17th October 2017) - Ma, Xinlong; Song, Xinyu; Tang, Yushu; Qi, Chuanlei; Ning, Guoqing; Gao, Jinsen; Li, Yongfeng
Abstract: The intercalation of CoO nanoparticles (NPs) in S‐graphite (labeled as CoO@S–graphite) composite is obtained by a one‐step doping reaction between graphite and CoSO4 in a fluidized bed reactor. CoO@S–graphite presents increased specific surface area and higher intensity ratio of the D to G band compared with the pristine graphite owing to the etching effect during the calcination treatment. As an anode material for lithium‐ion batteries, the enhanced energy‐storage ability of the as‐synthesized compound is a result of the S doping and CoO NPs intercalation, which not only contributes to enhancing the rate capability, but also has no impact on the outputs of delithiation capacity and voltage plateau below 0.5 V. The configured CoO@S–graphite/LiFePO4 battery exhibits better rate capability than that based on graphite/LiFePO4 and affords a high reversible capacity of 160 mAh g −1 at 0.2C and excellent durability. Abstract : Co‐effect on graphite : An anode material consisting of a CoO@S–graphite intercalated compound is derived from a one‐step calcination process without any purification based on the doping–intercalation methodology. This type of intercalation not only has no effect on the output of the delithiation voltage plateau below 0.5 V but also contributes to an enhanced Li storage capacity and rate capability.